Challenges and Opportunities of Transition Metal Oxides as Electrocatalysts. Issue 5 (16th December 2022) - Xiong, Wei; Yin, Huhu; Wu, Tianxing; Li, Hao
Abstract: As a sustainable energy technology, electrocatalytic energy conversion and storage has become increasingly prominent. The oxygen reduction reaction (ORR), oxygen evolution reaction (OER), hydrogen evolution reaction (HER), nitrogen reduction reaction (NRR), and carbon dioxide reduction reaction (CO2 RR) are the key steps in the industrial applications of energy conversion and storage. Compared to the widely used precious metal catalysts, less‐noble transition metal oxides (TMOs) and TMO‐like materials have attracted broad attention as electrocatalysts in the above reactions. In this concept, we summarize the challenges and opportunities of some typical TMOs in electrocatalysis, and modification strategies of TMOs as electrocatalysts are discussed. Abstract : Improving TMOs : The search for transition metal oxide (TMO) electrocatalysts is important but challenging. TMO electrocatalysts have the advantage of low cost, but also inherent disadvantages, such as poor electron conductivity. To meet industrial demands, better TMOs need to be identified by extensive searching, catalyst design, and structural engineering.